PM2.5 exposure exacerbates allergic rhinitis in mice by increasing DNA methylation in the IFN-γ gene promoter in CD4+T cells via the ERK-DNMT pathway. (February 2019) - Li, Youjin; Zhou, Ji; Rui, Xiaoqing; Zhou, Lin; Mo, Xi
Graphical abstract: Highlights: PM2.5 exposure exacerbates AR in mice. PM2.5 regulates the polarization of the Th1/Th2 balance by epigenetic regulation. The ERK-DNMT pathway was involved in epigenetic regulation of PM2.5. Abstract: Allergic rhinitis (AR) is a common chronic inflammatory disease that has a significant impact on the quality of life of patients. Our previous study suggested that PM2.5 might affect pediatric AR through epigenetic regulation, but the underlying mechanisms remained unclear. In this study, an experimental murine AR model was created, and the nasal symptoms, pathological changes, the DNA methylation level of the IFN- γ gene promoter and activation of the ERK-DNMT pathway were evaluated after treatment with PM2.5. Our results showed that PM2.5 exposure led to more severe symptoms of AR in mice. In addition, PM2.5 exposure significantly decreased the percentage of Th1 T cells in the AR group, and this change was correlated with increased DNA methylation of the IFN-γ gene promoter in CD4 + T cells (r=-0.916, p = 0.029). In addition, PM2.5 exposure increased the activation of the ERK-DNMT pathway in CD4+ T cells, and inhibiting this effect rescued the polarization of the Th1/Th2 balance toward Th2, thereby decreasing the risk of AR. Our findings demonstrate that PM2.5 exposure could exacerbate AR by increasing the DNA methylation of the IFN-γ gene promoter in CD4 + T cells via the ERK-DNMT pathway, and these effects were rescued when the ERK-DNMT pathway was inhibited.